Extended anticoagulation for unprovoked venous thromboembolism - Castellucci, Lana A. (Res Pract Thromb Haemost, 2018)
After completing anticoagulation therapy for acute venous thromboembolism (VTE), patients with unprovoked VTE are at increased risk of recurrent thrombotic events. Recent studies suggest a risk of nearly 10% in the first year after stopping anticoagulants and 30% at 8 years. Therefore, it is important to consider extended anticoagulation for secondary prevention in these high‐risk patients. While several oral anticoagulants are available for this purpose, there is limited information available regarding the optimal agent to minimize bleeding risks and maximize efficacy at VTE prevention. This review article summarizes the evidence available for Vitamin‐K antagonists (VKAs) and direct oral anticoagulants (DOACs) for extended treatment of VTE. We also introduce the COVET trial, the first head‐to‐head comparison of VKAs to DOACs, rivaroxaban and apixaban, for extended management of unprovoked VTE.